New Reality of the Banking Market: E-Banking and M-Banking (The Russia Case Study) - LUBKOVA, Elmira Minnullovna; SHILOVA, Anna Eduardovna; ERMOLAEVA, Galina Sergeevna (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
This research describes features of the development of Internet banking and mobile banking in the retail segment of the Russian banking market. Data on the share of remote access accounts opened in credit institutions for individual customers and the dynamics of payments using e-banking and banking is analyzed. Features of the development of e-banking and m-banking in Russian federal districts are considered. The comparison of the banking system in 2014 and in 2018 is presented. Features and problems of the development of e-banking and m-banking in Russia are revealed.